2022
DOI: 10.1038/s41598-022-11127-6
|View full text |Cite
|
Sign up to set email alerts
|

Springback effect and structural features during the drying of silica aerogels tracked by in-situ synchrotron X-ray scattering

Abstract: The springback effect during ambient pressure drying of aerogels is an interesting structural phenomenon, consisting of a severe shrinkage followed by almost complete re-expansion. The drying of gels causes shrinkage, whereas re-expansion is believed to be linked to repelling forces on the nanoscale. A multi-scale structural characterization of this significant volume change is key in controlling aerogel processing and properties. In this work, hydrophobic, monolithic silica aerogels with high specific surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 44 publications
1
17
1
Order By: Relevance
“…The calculated densities were in the range of typical values for silica aerogels reported in the literature by helium pycnometry. 20,24 These findings emphasized the reliability of the μCT quantitative imaging procedure and the accuracy of the underlying model for the modified gels. It is pertinent to be aware about the impact of potential closed pores in the calculation of the skeleton volume.…”
Section: ■ Results and Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…The calculated densities were in the range of typical values for silica aerogels reported in the literature by helium pycnometry. 20,24 These findings emphasized the reliability of the μCT quantitative imaging procedure and the accuracy of the underlying model for the modified gels. It is pertinent to be aware about the impact of potential closed pores in the calculation of the skeleton volume.…”
Section: ■ Results and Discussionmentioning
confidence: 80%
“…This suggested that the drying rate was only limited by the convection of hexane vapor within the drying chamber for the first 6 h. A previous study reported an increasing evaporation rate in similar gels, which may be related to a difference in the ambient conditions compared to this study. 24 Interestingly, we calculated a significant amount of gas phase in all gels already before the maximum shrinkage, making for up to 37 vol % of the gel's volume (Figures 6 and 7 and Figure S17). This suggested that the liquid−gas interface already receded into the pores, whereas common drying models predict that the liquid recedes in the pores once shrinkage stops.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
See 3 more Smart Citations